Agency and ideology in language maintenance: Hungarian immigrants' narratives on assimilationist post-war Australia. Issue 4 (1st October 2020) - Hatoss, Anikó
ABSTRACT: This study explored stories of intergenerational language maintenance narrated by first- generation Hungarian immigrants in Australia. It sought an understanding of Hungarian immigrants' positioning vis-à-vis their language ecology during the assimilationist post-war era of Australia. The narratives reveal that some families accepted the monolingual norms of using English in public spaces and gave in to the pressures of homogenising schools. However, in some families, agency was deployed to resist these normalising monolingual ideologies. These families had stronger intergenerational language maintenance of Hungarian. The findings of this research contribute to our understanding of the interactions between external factors (such as policy), and the subjective factors such as the individuals' agency in managing language use in immigrant contexts. The study discusses the way ideologies were shaped and negotiated and highlights the benefits of using linguistic narratives to reveal variability within seemingly homogenous communities.